Abatacept inhibits radiographic progression in patients with rheumatoid arthritis: a retrospective analysis of 6 months of abatacept treatment in routine clinical practice. The ALTAIR study. Issue 1 (January 2014) - Kubo, Satoshi; Saito, Kazuyoshi; Hirata, Shintaro; Fukuyo, Shunsuke; Yamaoka, Kunihiro; Sawamukai, Norifumi; Nawata, Masao; Iwata, Shigeru; Mizuno, Yasushi; Tanaka, Yoshiya
Abstract: Objectives Our objectives in this study were to determine the inhibitory effects of abatacept on joint damage and its clinical efficacy and safety in patients with rheumatoid arthritis (RA). Methods Fifty Japanese patients with RA were treated with abatacept for 24 weeks in routine clinical practice. Results At week 24, 20 % of patients achieved clinical remission [Simplified Disease Activity Index (SDAI) ≤3.3], whereas 50 % were in remission or had a low disease activity. Structural remission [progression of modified total Sharp score (ΔmTSS) ≤0.5] was achieved in 76 % of patients. The ΔmTSS decreased significantly from 7.1 ± 7.3 at baseline to 1.8 ± 5.7 at week 24. C-reactive protein (CRP) was the only independent prognostic factor for joint damage progression at week 24, whereas SDAI and matrix metalloproteinase-3 levels were not. A very high proportion of patients with CRP levels <1.5 mg/dl (88 %) achieved structural remission. In terms of safety, the retention rate for all patients was favorable (80 %), and stomatitis was the only adverse event observed. No patient withdrew from the study because of infections. Conclusions Abatacept has favorable clinical and structural effects, inhibits radiographic progression, and has a good safety profile in routine clinical practice.